Comparison of ion-exchange resins for efficient cobalt(II) removal from acidic streams. Issue 9 (2nd September 2018) - Wołowicz, Anna; Hubicki, Zbigniew
ABSTRACT: The ion-exchange method was applied for cobalt(II) removal from acidic streams using Lewatit MonoPlus TP 220, Purolite A 830, Lewatit SR 7, Purolite S 984, Purolite A 400 TL, Lewatit AF 5, Dowex PSR 2, and Dowex PSR 3. The effects of phase contact time, acid concentration, initial Co(II) concentration, and temperature were evaluated. The cobalt(II) desorption, ion exchanger reuse, and attenuated total reflection with the Fourier transform infrared spectroscopy, column studies were also performed. Lewatit MonoPlus TP 220 exhibits the highest sorption capacities and sorption follows the pseudo-second-order kinetics. The Freundlich model fitted the experimental data adequately. Desorption of cobalt(II) loaded is not quantitative. Sorption capacity reduction after three cycles of sorption–desorption (static method) was not observed.